Characterization of the dynamic mechanical properties of sisal fiber reinforced PET composites; Effect of fiber loading and fiber surface modification. Issue 9 (November 2021) - Gudayu, Adane Dagnaw; Steuernagel, Leif; Meiners, Dieter; Gideon, Rotich
Dynamic mechanical analysis (DMA) is an essential procedure for characterizing the performance of composites and effectively simulate with the real-world applications. This research work aims to characterize the dynamic mechanical (DM) properties of sisal fiber reinforced polyethylene terephthalate (PET) composites as a factor of fiber content and fiber surface modification. The effect of elevated processing temperature (>260°C) on the thermal degradation of sisal fibers is also analyzed. To study the effect of sisal fiber loading, PET composite specimens; one with 25% by weight fraction of raw sisal fiber (w/w), abbreviated as 25% RSC and the other with 40% by weight fraction (w/w) of raw sisal fiber, hereafter abbreviated as 40% RSC, were prepared by injection molding. Similarly, to analyze the impact of fiber surface modifications, PET composite samples containing 40% by weight fraction (w/w) of alkali-treated sisal, hereafter abbreviated as (40% Al-SC), and 40% by weight fraction (w/w) of a combined alkali/acetylation-treated sisal, hereafter abbreviated as (40% Al-ASC), were prepared. It was found that the fiber volume fraction and fiber surface modifications affected the DM properties of the produced composites. The improved storage module and glass transition temperature (Tg) with minimized damping has been demonstrated by increasing fiber content. With the same 40% fiber content, the composites produced from modified fibers enhanced the storage modulus and Tg values. However, with increasing temperature, the storage modulus decreased, the loss modulus increased, and the damping factor increased with composites containing higher fiber content and surface modified fibers. This indicates the low thermal stability of the sisal fiber and the interface damage at elevated temperatures.